Employee-Perceived Benefits of Training and Affective Commitment to Change: The Mediation Effect of Individual Readiness for Change - Muhammad, Eizel Mauldy; Tjahjono, Heru Kurnianto (Yayasan Riset dan Pengembangan Intelektual, 2024)
This research explores the relationship between employees' perceived training benefits and affective commitment to change in an organizational context. In addition, this study examines the mediating role of individual readiness for change in this relationship. This study is a multiple correlational research. In this study, a explanatory-quantitative approach will be used. The Structural Equation Modeling (SEM) analysis technique is used to test the proposed hypotheses using AMOS version 26 software. the population comprises 596 employees, data will be collected using the purposive sampling technique, therefore, this study will have a sample size of 100 participants. The results of this study revealed that employee perceived training benefits had no direct impact on affective commitment to change, but significantly influenced affective commitment to change indirectly through individual readiness for change. The implications of this study emphasizing the need for customized training programs and change management strategies, especially in the context of the oil & gas sector.